A Problem-Oriented Progressive Teaching Method for Undergraduates to Learn Logistics Distribution Center Planning and Management Course : Taking Location Problem as an Example - Sun, Yan (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
Logistics distribution center planning and management is the core course of the undergraduates majored in logistics management. It covers various optimization problems in the logistics planning field, and yields a significant systematism and a wealth of knowledge. In order to guide undergraduates to effectively learn this course, the teaching can be oriented on the classical planning problems that can integrates the large amount of knowledge from different chapters of the textbook. Since the undergraduates majored in logistics management are weak in mathematical modelling and computer programming, the progressive teaching method can be used to help them to improve these abilities gradually when learning to solve the problems. This study takes the logistics distribution center location problem as an example and systematically discuss the course design for teaching this problem based on the problem-oriented progressive method. As the first step of this research method, this research focuses on the design and teaching of basic problems with a view to introducing location problems to the students.